COMPETENCE INFLUENCE AND MOTIVATION ON EMPLOYEE PERFORMANCE WITH EMPLOYEE ENGAGEMENT AS A MEDIATION VARIABLE: Study on employee of Balai Wilayah Sungai Kalimantan I Pontianak - Purnomo, Eddy (Jurnal Ekonomi STIEP, 2023)
ABSTRACT This research is aim to determine the influence of employee competence and motivation on employee performance through employee engagement, as a mediation variable, as a case study on employees of the Kalimantan River Region Hall I Pontianak. Research Model is descriptive and associative quantitative. Data is obtained from questioners to employees as respondents. The number of respondents was 61 civil servants. The analytical method used is path analysis. The results obtained showed that competence has a significant effect on employee performance through employee engagement as a mediation variable, and conversely motivation does not significantly effect on employee performance, through employee engagement as a mediation variable. Pandemic Covid-19 makes limited in conducting direct interviews for questioner fillers, so the filling of questionnaires is less transparency and accountability. Keywords: Competence, Motivation, Employee Engagement, and Employee Performance